Birch house: A future vernacular architecture - Carlsson, Alexandra (My University, 2023)
This thesis investigates and showcases how Birch can be useful as a building material. From the standpoint of past vernacular architecture, a new way of building and use of materials is created. As a result, a proposal for a future vernacular architecture made out of 90% birch materials is presented. The goal is to showcase a new way of thinking regarding construction materials and processing as well as a user-friendly way of building in wood.